Morphology of Hobagella saltata n. gen. and n. sp. (Syndiniophyceae, Miozoa) infecting the marine dinoflagellate Cucumeridinium coeruleum (Dinophyceae, Miozoa) and its potential onshore advection - Yoo, Jiae; Kim, Sunju; Coats, D. Wayne (Frontiers in Marine Science, 2024)
Over the past decade, molecular phylogenies have placed endoparasites of the genus Euduboscquella in a distinct subclade within clade 4 of the Marine Alveolate (MALV) Group I . Recently, however, rRNA gene sequences have become available for four novel Euduboscquella-like species that infect dinoflagellates, with phylogenies including these sequences indicating that the genus Euduboscquella is paraphyletic. Here, we provide a morphological characterization of the intracellular and extracellular life-cycle stages of a novel species that infects Cucumeridinium coeruleum, a warm water pelagic species sometimes found in coastal environments. We formally describe the novel parasite, Hobagella saltata n. gen, n. sp., and identify a constellation of morphological and developmental characters that distinguish it, as well as Euduboscquella melo and E. nucleocola, both parasites of dinoflagellates, from Euduboscquella species that infect ciliates. We recommend the reassignment of E. melo and E. nucleocola as Hobagella melo n. comb. and H. nucleocola n. comb., respectively. We also propose the family Hobagellidae for these three congeners. We anticipate that the character set developed for distinguishing species of Euduboscquella and Hobagella will be valuable for sorting other Euduboscquella-Hobagella-like taxa scattered across the Group I phylogeny and will provide insight into morphological evolutionary patterns within Group I. Lastly, we consider the potential influence of summer-fall typhoons on the occurrence of H. saltata and its host C. coeruleum in near-shore waters along the southeastern coast of Korea and propose a hypothesis regarding the northward transport and onshore advection of host and parasite populations. If future research supports the hypothesized mechanisms, it could help us better understand parasite distribution and potential changes in biogeography associated with ongoing global changes in surface seawater temperature.